Primary osteosarcoma of bladder diverticulum mimicking intradiverticular calculus: a case report - Trnski Davor; Džombeta Tihana; Tomas Davor; Leniček Tanja; Grubišić Igor; Tomašković Igor; Krušlin Božo (BMC, 2011)
Abstract There is a well-documented relationship between urinary bladder diverticula and intradiverticular neoplasms. The great majorities of these tumors are urothelial carcinomas, but may also be of glandular or squamous type. Sarcomas occurring within bladder diverticula are exceptionally rare and highly malignant lesions, with only 20 well documented cases published in the literature to date (including carcinosarcomas). We report a case of osteosarcoma of the bladder diverticulum in a 68-year old man, which clinically mimicked intradiverticular calculus. To our knowledge, this is the second case described in the literature to date, and the first in English literature.